2003
DOI: 10.2169/internalmedicine.42.150
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Shortening of Peripheral Blood Mononuclear Cells in Coronary Disease Patients with Metabolic Disorders.

Abstract: Objective Telomere shortening is correlated with cell turnover and aging, but it has been recently suggested to occur not only by aging but by several biochemical fac- Results The results demonstrated that HCand/or DM patients with coronary diseases have significantly shorter telomere length than healthy controls (p=0.0014). Conclusion Telomere shortening may be involved in the mechanismsthat promote coronary diseases under some circumstances of metabolic disorders. (Internal Medicine 42: 150-153, 2003)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 20 publications
(19 reference statements)
3
25
0
1
Order By: Relevance
“…Our data are in line with recent studies showing that enhanced telomere attrition is associated with atherosclerosis (23,24). Accelerated telomere erosion was found in diabetic patients (25)(26)(27). This is confirmed here; however, as evidenced by our disease control subjects, acceleration of telomere attrition is independent of type 2 diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…Our data are in line with recent studies showing that enhanced telomere attrition is associated with atherosclerosis (23,24). Accelerated telomere erosion was found in diabetic patients (25)(26)(27). This is confirmed here; however, as evidenced by our disease control subjects, acceleration of telomere attrition is independent of type 2 diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, several studies have demonstrated a relationship between telomere length in peripheral blood leukocytes (PBL) and the onset of certain diseases associated with aging. Such studies in nonneoplastic diseases have shown that PBL telomere lengths can provide predictive information on the risk of developing atherosclerosis (87,88) and on overall mortality (89). In aggregate, these data indicate that although telomerase plays a clear role in malignant progression, telomere-induced checkpoints also contribute to certain aspects of human aging.…”
Section: Figurementioning
confidence: 94%
“…One strength of this study is that the diabetic group was selected to limit confounding by variables that influence telomere length such as age, sex, ethnicity, drug therapy, smoking, and inflammatory processes such as established vascular disease or hypertension, which make clinical studies on telomere length less easy to interpret (1)(2)(3)(15)(16)(17)(18)(19)23,24). Monocyte-endothelial cell adhesion is enhanced in type 2 diabetes (35), and in other studies we have shown that monocytes from type 2 diabetic subjects demonstrate increased adhesion molecule expression during glycemic excursions and increased expression of the LDL scavenger receptor, CD36 (36,37).…”
Section: Determinants Of Telomere Length In Control Subjectsmentioning
confidence: 99%